The emerging roles of hnRNPK. Issue 3 (19th September 2019) - Wang, Ziyi; Qiu, Heng; He, Jianbo; Liu, Langxia; Xue, Wei; Fox, Archa; Tickner, Jennifer; Xu, Jiake
Abstract: Heterogeneous nuclear ribonucleoprotein K (hnRNPK) is an DNA/RNA‐binding protein and regulates a wide range of biological processes and disease pathogenesis. It contains 3 K‐homologous (KH) domains, which are conserved in other RNA‐binding proteins, mediate nucleic acid binding activity, and function as an enhancer or repressor of gene transcription. Phosphorylation of the protein alters its regulatory function, which also enables the protein to serve as a docking platform for the signal transduction proteins. In terms of the function of hnRNPK, it is central to many cellular events, including long noncoding RNA (lncRNA) regulation, cancer development and bone homoeostasis. Many studies have identified hnRNPK as an oncogene, where it is overexpressed in cancer tissues compared with the nonneoplastic tissues and its expression level is related to the prognosis of different types of host malignancies. However, hnRNPK has also been identified as a tumour suppressor, as it is important for the activation of the p53/p21 pathway. Recently, the protein is also found to be exclusively related to the regulation of paraspeckles and lncRNAs such as Neat1, Lncenc1 and Xist. Interestingly, hnRNPK has been found to associate with the Kabuki‐like syndrome and Au‐Kline syndrome with prominent skeletal abnormalities. In vitro study revealed that the hnRNPK protein is essential for the formation of osteoclast, in line with its importance in the skeletal system. Abstract : Heterogeneous nuclear ribonuclearprotein K (hnRNPK) is a DNA/RNA‐binding protein involved in many biological processes. It has been found to be associated with long noncoding RNA (lncRNA) regulation, cancer, developmental and skeletal biology. Studying the function of hnRNPK provides better understanding of the protein–protein and protein–DNA/RNA interaction, hence a better understanding of related pathological conditions.